[68Ga]PSMA-HBED-CC Uptake in Osteolytic, Osteoblastic, and Bone Marrow Metastases of Prostate Cancer Patients. - Janssen, Jan-Carlo; Woythal, Nadine; Meißner, Sebastian; Prasad, Vikas; Brenner, Winfried; Diederichs, Gerd; Hamm, Bernd; Makowski, Marcus; Makowski, Marcus R (Molecular Imaging & Biology, 2017)
Purpose: The aim of this study was to evaluate potential differences in "Glu-NH-CO-NH-Lys" radio-labeled with [68Ga]gallium N,N-bis[2-hydroxy-5-(carboxyethyl)benzyl]ethylenediamine-N,N-diacetic acid ([68Ga]PSMA-HBED-CC) uptake in osteolytic, osteoblastic, mixed, and bone marrow metastases in prostate cancer (PC) patients.Procedures: This retrospective study was approved by the local ethics committee. Patients who received [68Ga]PSMA-HBED-CC positron emission tomography/computed tomography ([68Ga]PSMA-PET/CT) with at least one positive bone metastasis were included in this study. Only patients who have not received systemic therapy for their PC were included. Bone metastases had to be confirmed by at least one other imaging modality or follow-up investigation. The maximum standardized uptake value (SUVmax) and mean Hounsfield units (HUmean) of each metastasis were measured. Based on CT, each metastasis was classified as osteolytic (OL), osteoblastic (OB), bone marrow (BM), or mixed (M).Results: One hundred fifty-four bone metastases in 30 patients were evaluated. Eighty out of 154 (51.9%) metastases were classified as OB, 21/154 (13.6%) as OL, 23/154 (14.9%) as M, and 30/154 (19.5%) as BM. The SUVmax for the different types of metastases were 10.6 ± 7.07 (OB), 24.0 ± 19.3 (OL), 16.0 ± 21.0 (M), and 14.7 ± 9.9 (BM). The SUVmax of OB vs. OL and OB vs. BM metastases differed significantly (p ≤ 0.025). A significant negative correlation between HUmean and SUVmax (r = -0.23, p < 0.05) was measured.Conclusions: [68Ga]PSMA-HBED-CC uptake is higher in osteolytic and bone marrow metastases compared to osteoblastic metastases. Information derived from [68Ga]PSMA-PET and CT complement each other for the reliable diagnosis of the different types of bone metastases in PC patients.